Assessment of the potential for small-scale CHP production using Organic Rankine Cycle (ORC) systems in different geographical contexts: GHG emissions impact and economic feasibility. (November 2022) - Cruz, Igor; Johansson, Maria T.; Wren, Joakim
Abstract: According to the European Commission's 2050 Climate Strategy, renewable electricity is the most important driver for decarbonising the energy system. The intermittent nature of wind and solar creates a demand for dispatchable electricity production that can contribute to a stable and steady supply all year. This supply can be provided, for example, by biomass boilers with combined heat and power production. This paper analyses the potential for small-scale electricity production in Organic Rankine Cycle systems (ORC) in different geographical contexts. The focus is on installing ORC systems with existing biomass-fired boilers in district heating (DH) systems or industry, and with industrial excess heat streams. Economic and climate effects are studied in three countries with different climates and energy-market conditions, namely Sweden, the United Kingdom and Brazil. The results show that there is the potential to install ORC systems around the world that are both economically viable and reduce global greenhouse gas emissions. Equipment size has a large effect on the profitability of the investments. Moreover, the benefits of tax exemptions and certificates for renewable electricity production significantly impact profitability, particularly for smaller equipment sizes.